THE TRAINING OF PHARMACY PROFESSIONALS AND THEIR EDUCATIONAL CONTRIBUTIONS IN BREAST CANCER CARE (CIPEEX, 2025)
Introduction: The training of pharmacy professionals, over the last decades, has consolidated as a scientific, technical, and social field, guided by interdisciplinarity and the integration of knowledge involving biomedicine, chemistry, professional ethics, and health education. In the context of oncology, especially in breast cancer treatment, pharmacists play a key role both in therapeutic follow-up and in educational practices directed at patients, families, and communities. In this scenario, pharmacists contribute not only to the management of medicines used in chemotherapy, hormone therapy, and targeted therapies but also to educational practices that support treatment adherence, prevention of adverse effects, and the promotion of quality of life. Objectives: This study aims to analyze the importance of pharmaceutical training in breast cancer treatment; discuss the educational dimension of pharmacists’ work in oncology; and highlight counseling and therapeutic follow-up practices that strengthen treatment adherence and health promotion. Methodology: This is a bibliographic and descriptive study based on the analysis of scientific articles, institutional documents, and public health policy guidelines. Justification: The pharmacist, as part of multidisciplinary teams, contributes to medication safety, clarifies doubts about therapeutic regimens, and promotes health education. The appreciation of this formative and educational aspect is justified by the potential to expand access to information, reduce treatment-related risks, and support the building of trust between professionals and patients. Results and Discussion: The analysis of the consulted sources shows that pharmacists’ work in oncology has progressively expanded, evolving from the technical role of compounding and dispensing medicines to an active role in educational and follow-up actions. Pharmaceutical counseling programs in oncology services indicate significant improvement in treatment adherence, greater understanding of chemotherapy side effects, and better patient quality of life. Furthermore, experiences reported in health services highlight that educational practices, such as group discussions and individualized counseling, contribute to strengthening patients’ shared responsibility in the care process. Conclusion: The training and practice of pharmacists in breast cancer treatment highlight the importance of integrating science, education, and care. It is concluded that investing in the pedagogical and communication training of these professionals is essential to expand their contribution to prevention, follow-up, and coping with breast cancer, consolidating the pharmacist as a strategic agent in health promotion.